Combination of Photothermal Therapy with Anti‐Inflammation Therapy Attenuates the Inflammation Tumor Microenvironment and Weakens Immunosuppression for Enhancement Antitumor Treatment. Issue 13 (6th February 2022) - Zhang, Di; Yang, Jinghong; Ye, Sheng; Wang, Yutong; Liu, Chuang; Zhang, Qianbing; Liu, Ruiyuan
Abstract: Photothermal therapy has gained widespread attention in cancer treatment, although its efficacy is suppressed due to the inflammatory response and immunosuppression, resulting in a discounted therapeutic effect. In this contribution, a high‐performance NIR absorption organic small chromophore is developed, which is encapsulated into Pluronic F‐127 to fabricate NIR absorption organic nanoparticles (TTM NPs) with excellent photothermal conversion efficiency (51.49%) for photothermal therapy. TTM NPs based photothermal therapy are combined with Aspisol, a kind of nonsteroidal anti‐inflammatory drug, to weaken the inflammation and immunosuppression tumor microenvironment and enhance the antitumor effect. The results prove that the combination therapy realizes effective thermal elimination of primary tumors, inhibition of distant tumors, and suppression of tumor metastasis. The data show that combination therapy can suppress the expression of inflammatory factors, enhance dendritic cell activation and maturation, reverse the immunosuppression, facilitate T cell infiltration, and restore antitumor cytotoxic T lymphocyte activity. This study provides a paradigm to extend the development of photothermal therapy. Abstract : This paper reports an innovative NIR absorbing organic small chromophore (TTM) encapsulated into TTM NIR absorption organic nanoparticles by Pluronic F‐127 with high photothermal conversion efficiency (51.49%) for photothermal therapy. TTM NPs based photothermal therapy is combined with Aspisol to attenuate the inflammation and immunosuppression, realize effective thermal ablation of the primary tumor, inhibit distant tumors, and suppress tumor metastasis.